Non–traditional Machining of Inconel 600 Material - Kartal, Fuat; Hloch, Sergej (Springer International Publishing, 2018)
Abrasive water jet machining (AWJM) is successfully used for various industrial applications to cut extreme ductile and brittle materials. Thermal deterioration, high processing diversity, provide distinct advantages with high flexibility and small cutting forces. In this study, the Taguchi design analysis was used to determine the optimal combination of parameters for the actual cutting conditions of the Inconel 600 material. Variance Analysis (ANOVA) was also used to determine the most important factor. Common parameters such as nozzle feed rate, nozzle standoff distance and abrasive flow rate are optimized to investigate the effects of parameters on the Surface Roughness (Ra) during cutting of the Inconel 600 material.